RESPONSE TIME OF NURSES WITH COMPLAINT HANDLING FROM THE FAMILIES OF TRAFFIC ACCIDENT PATIENTS AT THE EMERGENCY INSTALLATION AT THE DUMAI CITY HOSPITAL IN 2020 (Al Insyirah International Scientific Conference on Health, 2021)
Complaint handling is one of the factors that affect the quality and satisfaction of clients. The purpose of this study was to determine the relationship between nurse response time and complaint handling from the family of traffic accidents in nursing services at the emergency Installation in Dumai city Hospital.  The research design was a correlational study with 98 respondents. The sampling technique was purposive sampling. The results of the univariate analysis of respondents had good complaint handling with a total of 60 people (75.9%) and respondents thought the response time of nurses was fast enough with a total of 61 people (77.2%). The results of the Spearman rank test analysis showed that there was a relationship between the response time of nurses and complaint handling in the emergency room at the Dumai city Hospital ( p = 0.000
Keywords: complaint handling; Emergency Room; Nurse Response Time